Piezotronic effect and oxygen vacancies boosted photocatalysis C‒N coupling of benzylamine. (May 2021) - Wang, Penglei; Li, Xinyong; Fan, Shiying; Yin, Zhifan; Wang, Liang; Tadé, Moses O.; Liu, Shaomin
Abstract: Photocatalytic selective oxidation of benzylamine into high-value-added organic intermediates holds great promise. Herein, to achieve the goal of efficient separation of photo-generated electrons/holes and regulation of abundant active sites, we systematically investigated the synergistic impact of piezotronic effect and oxygen vacancies on selectively aerobic oxidation of benzylamine into N-benzylidenebenzylamine with Bi4 NbO8 Br single-crystalline nanosheets (BNO). We found that piezotronic effect and oxygen vacancies could collaboratively enhance the separation of photogenerated electrons and holes. Furthermore, theoretical calculations and experimental results demonstrated that oxygen vacancies can also optimize the adsorption and activation of O2 and benzylamine molecules to favor the efficient conversion of which. As a result, the conversion rates of benzylamine increased by about 2.1 times owing to the presence of piezotronic effect and oxygen vacancies. The present work opens an avenue for enhancing photocatalytic activity in selective oxidation of organic pollutant into value-added products, and also shed light on an understanding for the design of a highly efficient multi-field catalytic system in the future. Graphical Abstract: ga1 Highlights: Bi4 NbO8 Br nanosheet oriented along the [001] direction with oxygen vacancies were successfully synthesized. Piezotronic effect and oxygen vacancies can synergistically enhanced photocatalytic activity for aerobic oxidation of benzylamine. Cooperative mechanism of piezotronic effect and oxygen vacancies in promoting photocatalytic activity was unveiled. This work provides an avenue and insight for developing efficient multi-field catalytic system.